2021
DOI: 10.3390/nu13093120
|View full text |Cite
|
Sign up to set email alerts
|

Eating Perception, Nutrition Knowledge and Body Image among Para-Athletes: Practical Challenges in Nutritional Support

Abstract: Limited information exists on dietary practices in para-athletes. The aim of this study was to clarify the actual situation of para-athletes’ dietary practice and to sort out the factors (i.e., eating perception, nutrition knowledge, and body image), that may hinder their dietary practices, and explored the practical challenges in nutritional support and improving nutrition knowledge for para-athletes. Thirty-two Japanese para-athletes (22 men) and 45 collegiate student athletes without disabilities (27 men) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 73 publications
0
7
0
1
Order By: Relevance
“…Correct nutrition guarantees energy needs and recovery during and after exercise [ 37 ], while insufficient nutrition can increase the risk of injury and illness and decrease performance [ 69 ]. Despite being scarce, studies on the nutritional knowledge of athletes with disabilities and its relationship with sport have increased [ 37 , 70 , 71 , 72 ], as this is also a key element for performance indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Correct nutrition guarantees energy needs and recovery during and after exercise [ 37 ], while insufficient nutrition can increase the risk of injury and illness and decrease performance [ 69 ]. Despite being scarce, studies on the nutritional knowledge of athletes with disabilities and its relationship with sport have increased [ 37 , 70 , 71 , 72 ], as this is also a key element for performance indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 18.5% had an elevated dietary restraint subscale score and 32.4% had elevated pathologic behavior subscale scores, as assessed by the Eating Disorder Examination Questionnaire (EDE-Q). A positive correlation between body image scores and ideal eating behavior was found in Japanese Para athletes [ 7 ]. This provides evidence that improved nutritional support, tailored to the needs of Para athletes, might result in improved body image and mental well-being.…”
Section: Other Factors Of Red-smentioning
confidence: 99%
“…Similar to able-bodied athletes, Para athletes face body image-related challenges [ 6 , 7 , 8 ] that can result in disordered eating behavior and clinical eating disorders. These issues are, along with unawareness of dietary needs and potential problems with sufficient fueling, known risk factors and/or causes of LEA [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only 3.5% of certified sports nutritionists jointly certified by the Japan Dietetic Association and the Japan Sports Association profess para-sports and para-athletes as their field [21]. Para-athletes themselves lack knowledge of sports nutrition [20,22], and it is reported that many of them are unable to practice dietary intake to meet their energy and nutrient demands [23]. In addition, various dietary problems caused by the types of disabilities and individual differences of para-athletes make nutrition support challenging.…”
Section: Introductionmentioning
confidence: 99%